2013
DOI: 10.1074/jbc.m112.410126
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4-Phosphate 5-Kinase α Facilitates Toll-like Receptor 4-mediated Microglial Inflammation through Regulation of the Toll/Interleukin-1 Receptor Domain-containing Adaptor Protein (TIRAP) Location*

Abstract: Background: Phosphoinositides are involved in regulating TLR4 signaling. Results: PIP5K␣ knockdown in BV2 microglial cells inhibits LPS-induced inflammatory responses, PIP 2 increase, and TIRAP translocation to the plasma membrane. Conclusion: PIP5K␣-derived PIP 2 facilitates TLR4-mediated microglial inflammatory responses through recruitment of TIRAP to the plasma membrane. Significance: Regulation of PIP5K␣-dependent PIP 2 pool may modulate TLR4-associated immune function in microglia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 63 publications
1
51
0
Order By: Relevance
“…Phosphorylation of PI(4,5)P 2 to PI (3,4,5)P 3 by the p110δ isoform of phosphatidylinositol 3-kinase serves as a switch from MyD88-to TRIF-dependent signaling (Aksoy et al, 2012), and PI(4,5)P 2 hydrolysis can also contribute to this switch (Chiang et al, 2012). It has recently been reported that LPS induces an increase of the PI(4,5)P 2 level in microglia by activating PIP5K Iα (Nguyen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of PI(4,5)P 2 to PI (3,4,5)P 3 by the p110δ isoform of phosphatidylinositol 3-kinase serves as a switch from MyD88-to TRIF-dependent signaling (Aksoy et al, 2012), and PI(4,5)P 2 hydrolysis can also contribute to this switch (Chiang et al, 2012). It has recently been reported that LPS induces an increase of the PI(4,5)P 2 level in microglia by activating PIP5K Iα (Nguyen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, association of TIRAP to membranes is transient during TLR-mediated signaling. LPS-mediated activation of TLRs induces dynamic changes in PtdIns(4,5)P 2 and TIRAP translocation to the plasma membrane, where TIRAP is transiently located at the plasma membrane and moves to the cytosol 30 min after LPS stimulation 12 . TIRAP meets the general features of a peripheral membrane protein.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis and turnover of plasma membrane PtdIns(4,5)P 2 influences TIRAP subcellular localization. Membrane binding of TIRAP is regulated by phosphatidylinositol-5 kinase (PI5K), an enzyme that generates intracellular PtdIns(4,5)P 2 and co-localizes with TIRAP at the plasma membrane 12 . Moreover, TIRAP interacts with PI3Ks, enzymes that convert PtdIns(4,5)P 2 into PtdIns(3,4,5)P 3 , impairing TIRAP's membrane targeting 13 .…”
mentioning
confidence: 99%
“…The same group confirmed these initial observations by evidencing that a dominant-negative mutant of PIP5Ka impaired PIP2 production and the membrane recruitment of TIRAP in LPS-stimulated microglia. As a result, TLR4-associated signalling pathways and pro-inflammatory mediator production were both strongly inhibited [69]. Based on these observations, a role for PIP5K in regulating critical functions of macrophages, ranging from the ingestion and elimination of pathogens to the signals regulating the expression of genes involved in host defence from infection, can be envisaged (Fig.…”
Section: Macrophagesmentioning
confidence: 99%